Untied temporalities: the poetic gesture in the myth of Hélio Oiticica - Nakahara, Carolina Akemi Martins Morita (Revista ARA, 2023)
The notion of myth, part of the artist Hélio Oiticica's environmental program, drew attention for breaking both with linear and progressive representations of time and with a certain reactionary nostalgia typical of the 1960s, taking the utopia of the future against the grain, by rescuing the dialectical and poetic sense of work. This article proposes to resume and, thus, unleash new meanings of this creative power towards the possible.